Credit Shocks and Macroeconomic Fluctuations in Emerging Markets - Houssa Romain; Jolan Mohimont; Chris Otrok (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper, we examine the role of global and domestic credit supply shocks in macroeconomic fluctuations for Emerging Markets. For this purpose, we impose a set of zero and sign restrictions within a medium-scale Bayesian Vector Auto-Regressive model. Quarterly data from South Africa and G-7 countries in 1985-2010 show that credit supply shocks impact significantly on macroeconomic aggregates in these economies. However, credit supply shocks have played, on average, a less important role than credit demand shocks. Moreover, shocks originating from G7-countries are the main drivers of real activity in South Africa, although they played a marginal role in the 1996-1999 South African recession.
Keywords: C51; C33; C15; C53; E30; E43; E52; N17; 330; credit shocks; developing countries; macroeconomic stabilization policies; sign restrictions; Bayesian VAR